Functional affinities of man, monkeys, and apes : a study of the bearings of physiology and behaviour on the taxonomy and phylogeny of lemurs, monkeys, apes, and man /: a study of the bearings of physiology and behaviour on the taxonomy and phylogeny of lemurs, monkeys, apes, and man. (2019) - Baron, Zuckerman, Solly, 1904-1993
No abstract available